LIPID PROFILES IN CHILDREN AND ADOLESCENTS WITH TYPE 2 DIABETES MELLITUS - S, Nalini M; W, Sze Lyn Jeanne; L, Annie; T, Sze Teik; T, Pian; MA, Noor Arliena; M, Rashdan Zaki; MZ, Fuziah; H, Janet Yewhua (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION The incidence of Type 2 Diabetes Mellitus (T2DM) in children has increased significantly over the last two decades. T2DM is associated with high morbidity and mortality secondary to cardiovascular disease. This association has significant pathologic implications in paediatrics where earlier onset and accelerated progression of atherosclerosis has a profound impact on mortality and quality of life. METHODOLOGY The objective of this study was to evaluate dyslipidaemia in a paediatric population with T2DM. The electronic medical records (EMR) of patients under the age of 18 years (n=34) with T2DM and who were under the follow-up of the Paediatric Endocrine Unit, Hospital Putrajaya were reviewed. RESULTS The mean age of the population was 14.5 (2.5) years with median duration of diabetes 3[1.4–4.35] years. Mean age of onset of diabetes was 11 (1.8) years with the youngest age of onset at 8 years old. The patients were 61.8% female and 38.2% male. Mean BMI z-score was 2.1±0.05 and mean HBA1c was 9.6 (2.7). On complication screening 14.7% had hypertension, 26.5% had microalbuminuria, 55.8% of patients had an elevated LDL level and 35.3% had an elevated triglyceride level. BMI z scores were positively associated with elevated LDL and triglyceride level. Patients with a HbA1c >8% had a significantly higher total cholesterol, LDL and triglyceride level (p<0.05). CONCLUSION Increased HbA1C and BMI were associated with adverse lipid profiles in children and adolescents with T2DM. Therefore, poor glycaemic control and obesity represent two major modifiable factors to reduce cardiovascular risk in children with T2DM.